Staying with Complexity. Bidirectional Learning, Engagement, and Transdisciplinary Collaborations on Two Continents - Lambert-Pennington, Katherine; Saija, Laura (Antropologia Pubblica, 2024)
Over the last few decades, institutions of higher education in both The United States and Italy have intensified their attention, activities, messages toward building relationships with worlds outside of their campuses. Despite their best intentions, the relationship between institutions of higher education and non-academic actors, whether in the frame of engaged scholarship (US) or the third mission (Italy), often does not move beyond unidirectional and extractive interactions. In this paper, we draw on our experiences as an engaged anthropologist (Lambert-Pennington) and a Planner (Saija) working with residents of a public housing community in Memphis, TN and co-leading the Community Planning and Environmental Design (CoPED) program in the Simeto Valley (Sicily), to posit a transdisciplinary bidirectional praxis – one that combines participatory research and experiential pedagogy. We begin by comparing US engagement and Italian third mission debates and then briefly situate our own work within the literature on engaged praxis in our respective disciplines. We trace moments and dynamics in our work together that led us to emphasizes co-learning and bidirectionality - intentionally involving actors’ multiple perspectives and dimensions (spatial and socio-political), but also, and especially, to emphasize mutual benefits and co-learning to address local challenges. In the conclusion, we reflect on the